Analysis of the Stability of the Banking Sector of Azerbaijan in Conditions of Economic Crisis Based on the Econometric Model - S. M. Huseynova; T. Ja. Hajizada (Статистика и экономика)
This article is devoted to the influence of a number of macroeconomic indexes on the amount of reserves for possible losses in the Azerbaijan banking sector.The purpose of research. The purpose of the research to analyze the stability of the banking sector to the impact of macroeconomic shocks in the economy, study what the concept of financial stability of the banking sector includes, and what methods are used in the process of its analysis and assessment, investigate the dependence of a number of variables characterizing the state of the banking sector on various macroeconomic shocks inherent in the economy, analyze how the Central Bank is involved in regulating and monitoring the financial stability of the banking sector, as well as through what measures it supports banks in times of crisis.Materials and мethodology. The practical stage of the work is to create a multiple regression model that will reveal the degree of impact of macroeconomic shocks on the position of the Azerbaijan banking sector. To carry out the analysis and construct regression equations, quarterly data for the period 2012-2023 were used. Information was taken from a number of sources: 1) Official website of the Central Bank of Azerbaijan; 2) Official website of Ministry of Finance; 3) Official website of Azerbaijan State Statistics Committee; 4) Reports on the development of the banking sector and banking supervision. To analyze and estimating the values of the dependent variables of provisions for possible losses and return on assets, values for the banking sector as a whole are taken from annual reports on the development of the banking sector and banking supervision.Since the source data in the work is quarterly, our model will be a time series estimated using the ordinary least squares (OLS) method. Lagged variables may be included in the time series. The lags in the explanatory variables take into account the degree of possible lag with which macroeconomic shocks affect banks. In other words, changes in the values of macroeconomic factors do not have an immediate impact on the position of banks, but appear after some time and are delayed [7]. Such lags need to be identified and taken into account in order to form a more accurate and complete picture of the impact of macroeconomic fluctuations on the banking sector.During preliminary diagnostics of the data, the presence of heteroscedasticity and first-order autocorrelation was revealed. To eliminate it, Newey-West corrections are applied, adjusting the variation-covariance matrix to obtain more consistent estimates of regression coefficients.Results. When selecting indexes to study the degree of impact of macroeconomic factors on the stability of the banking sector, we took into account the peculiarities of the economy of our country. The fact is that Azerbaijan is a raw materials country, the export of which consists of almost 70% of fuel and energy products [30]. This means that the size of export revenues, the financial position of companies and the stability of the economy are highly dependent on the price situation in the global energy market, namely the price of oil.In addition, Azerbaijan belongs to a number of countries with an emerging market, which is characterized by increased volatility of exchange rates and instability of financial markets and high interest rates and spreads. Therefore, our country is characterized by the risk of a sharp outflow of capital in the event of a crisis in the world, as investors seek to withdraw their funds from countries that are most vulnerable to the influence of macroeconomic shocks.GDP dynamics are one of the important indicators of the economic activity of the state. Its fall during the crisis negatively affects various spheres of economic and social life [8].The Baku stock exchange index reflects the state of the stock market of large companies, which are the most important for the country’s economy [9]. The collapse of the index means a deterioration in the position of companies, a decrease in the market value of their assets and shares, and increases problems with paying external debt and obtaining new loans to ensure the functioning of their activities. In addition, the collapse of quotes on the stock market leads to large losses as a result of their negative revaluation.Conclusion. When conducting a research of the sustainability of the banking sector in Azerbaijan based on an econometric model, it is necessary to take into account certain limitations. First, the availability and reliability of data is an important aspect that can affect the accuracy of the study results. Secondly, to fully understand the issues under study, it is necessary to take into account the context and specifics of the banking system of Azerbaijan. Finally, this study does not examine social and political factors that may also influence the sustainability of the banking system. Limitations of the study should be considered when interpreting the results and making recommendations.